PENGARUH PENDIDIKAN NON FORMAL (TPA) TERHADAP PEMAHAMAN MATERI TENTANG AGAMA ISLAM - Gio Apriansyah; Mardeli Mardeli; Syarnubi Syarnubi; Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
Non-formal education is a systematic activity outside the school system that is useful for improving students' knowledge or understanding and achieving their learning goals. Non-formal education itself has the following characteristics: short-term education, more flexible registration requirements, a place to learn outside the classroom and inside the classroom, conditions that are not strict and are not limited to students and specific curricula. This study discusses the effect of non-formal education (TPA) on students' understanding of material about Islam in SD Negeri 83 Palembang. The formulation of the problem in this study are (1) What is the ability to understand Islam among students in SD Negeri 83 Palembang who do not attend non-formal education. (2) What is the ability to understand Islam among students in SD Negeri 83 Palembang who do not attend formal education. (3) What is the influence of non-formal education on the ability of students to understand Islamic religious education material.The variable in this study is non-formal education (x) and the dependent variable is the understanding of the material (y).To obtain the result of this study, the methods of written tests, documentation and questionnaires were used. Based on the obtained research results, non-formal education (TPA) affects the understanding of the material about Islam, because the test results of the experimental class are greater than the control class. The difference can be seen from the results of calculating the analysis using the T-test formula through the SPSS application, which shows the resulting significance is less than 0.05.